MOTIVASI INDONESIA EKSPOR CPO (CRUDE PALM OIL) KE TUNISIA TAHUN 2010-2014 - Friska Novianti; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This thesis is a Bilateral Trade study that provides an analysis of two-state Cooperation in meeting needs and achieving their interests. This research focused on the Export of Indonesian Palm Oil (CPO) to Tunisia from 2010-2014. Palm Oil is the product of processed palm oil as vegetable oil which is needed as industrial material and household consumption. Where Indonesia as the largest palm oil producer in the world accounts for 51% of the world's demand for palm oil and exports to various countries including Tunisia. This thesis uses a conceptual basis with the concept of International Economic Cooperation in which International Economic Cooperation is carried out to get together through the use of finance and technological resources from each partner. Supported by the level of analysis of the Nation State and the Liberalism Perspective. The concept leads to the method of qualitative methods and is assisted by Library Research as a source of information. The MoU on Cooperation between Indonesia and Tunisia is a manifestation of Indonesia's national interests, in which the bilateral cooperation of the two countries is the ultimate goal of profit. Therefore, CPO export cooperation is one of the many Indonesian exports to Tunisia to achieve the set trade value with a contribution of 63.3% of Indonesia's exports to Tunisia in 2010-2014. Keywords: Bilateral Trade, International Cooperation, Liberalism, Exports, Palm Oil.